DISCOVERY LEARNING BASED AR: A LEARNING INNOVATION TO ENHANCE CRITICAL THINKING FOR JUNIOR HIGH SCHOOL - Dwi Ayu Nurfaizah; Tia Sarawati; Sarina Sarina; Andini Pertiwi; Maryati Maryati; Ismail Fikri Natadiwijaya (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
Learning challenges include using innovative media to improve students' critical thinking skills. This research examined the effectiveness of AR based Discovery Learning as an innovative learning media to enhance students' critical thinking skills. This research employed a pre-experimental approach, specifically utilizing a one-group pretest-posttest design. The participants consisted of 28 seventh-grade students from junior high schools in Yogyakarta. A critical thinking skills test focused on Solar System content served as the research instrument. Data were analyzed using both descriptive and inferential statistical methods with the help of SPSS version 22.0 for Windows. The findings revealed that the average normalized gain (N-gain) in students' critical thinking skills was 0.6327 (medium category), significantly increasing after using AR-based Discovery Learning. The effect size for critical thinking skills is 4.31 (huge category), which indicates that AR, based on Discovery Learning, significantly affects these skills. Discovery learning involves learners actively in the discovery process to increase in-depth understanding of the material. AR media supports more interactive learning through real visualisation of objects. So that AR media based on Discovery Learning can be used as an innovative and technology-based science learning strategy.